Does Amount and Type of Activity Matter in Behavioral Activation? A Preliminary Investigation of the Relationship between Pleasant, Functional, and Social Activities and Outcome. Issue 4 (July 2015) - Hershenberg, Rachel; Paulson, Daniel; Gros, Daniel F.; Acierno, Ron
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Accumulating evidence supports behavioral activation (BA) as an effective stand-alone treatment for improving depression and related conditions, though little is known about the factors that influence positive outcomes. Such research is ripe for future dissemination and implementation efforts, particularly among vulnerable older adult populations in need of such efficacious and transportable treatments. Aims: Given the central but largely unexamined role that increasing activities plays in BA, we investigated the association between participation in weekly activities and treatment outcome. Method: As a preliminary study of this research question, we report on a sample of 20 older adults with symptoms of depression and complicated bereavement who completed 5 weeks of BA, pre- and posttreatment measures, and weekly planners of BA activities. All activities were coded as either functional or pleasurable (by participants) and if they were social in nature (by trained coders). Results: Overall, BA was associated with reductions in symptomatology. However, participants' total number of reported activities, and their relative proportion of functional, pleasurable, and social activities, did not significantly relate to their improvement in symptoms. Conclusion: One interpretation of the findings suggests that countering avoidance more generally, potentially independent of the specific type or total amount of activation activities, may be associated with amelioration of symptomatology.